HUBUNGAN ANTARA KOMITMEN ORGANISASI DAN IKLIM ORGANISASI DENGAN KEPUASAN KERJA KARYAWAN PADA PT. COCA COLABOTTLING INDONESIA MEDAN - JASMAN SYARIPUDDIN (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2014)
ABSTRACT The purpose of this study was to know the relationship between the organizational commitment with employees satisfaction, knowing the relationship between the organizational climate and employees satisfaction, and to find the relationship between the organizational commitment and organizational climate and employees satisfaction that interconnected among one and the other at Coca Cola Bottling Indonesia Medan Corporation.Partially, there is the influence of the organizational commitment to employees satisfaction of Coca Cola Bottling Indonesia Medan Corporation where rhitung equal to 0,556, while the organizational climate also effect on the employees satisfaction of Coca Cola Bottling Indonesia Medan Corporation where rhitung equal to 0.563. The value of coefficient of multiple correlation jointly between the organizational commitment and the organizational climate on employees satisfaction of Coca Cola Bottling Indonesia Medan Corporation obtained Rx1x2y = 0.612. The positive value means that if the organizational commitment and the organizational climate improved employees satisfaction will increase. Keywords: organizational commitment, organizational climate, employees satisfaction